Swipe, Pay, Repeat: E-Wallets, Financial Literacy, and the Consumer Lifestyle of Gen Z in Kupang - Natonis, Sari Angriany; Simanjuntak, Olaf Tri Wilopo; Riwu, Yonas Ferdinand (Jurnal Penelitian Ekonomi Dan Akuntansi, 2025)
This study delves into how financial literacy and the use of Fintech e-wallets shape the consumptive behavior of Generation Z in Kupang City. Employing a quantitative approach with 75 respondents, this research utilizes multiple linear regression analysis to examine the influence of these two factors, both partially and simultaneously. The findings indicate that both financial literacy and the use of Fintech e-wallets have a positive impact on the consumptive behavior of Generation Z in Kupang City. These results provide crucial insights into the dynamics of consumption in the digital age and highlight the vital role of financial understanding and payment technology in shaping the spending habits of younger generations.